Use of Major Histocompatibility Complex Class I/Peptide/β2M Tetramers To Quantitate CD8(+) Cytotoxic T Lymphocytes Specific for Dominant and Nondominant Viral Epitopes in Simian-Human Immunodeficiency Virus-Infected Rhesus Monkeys - Egan, Michael A. (American Society for Microbiology, 1999)
To evaluate the impact of the diversity of antigen recognition by T lymphocytes on disease pathogenesis, we must be able to identify and analyze simultaneously cytotoxic T-lymphocyte (CTL) responses specific for multiple viral epitopes. Many of the studies of the role of CD8(+) CTLs in AIDS pathogenesis have been done with simian immunodeficiency virus (SIV)- and simian-human immunodeficiency virus (SHIV)-infected rhesus monkeys. These studies have frequently made use of the well-defined SIV Gag CTL epitope p11C,C-M presented to CTL by the HLA-A homologue molecule Mamu-A*01. In the present study we identified and fine mapped two novel Mamu-A*01-restricted CTL epitopes: the SIVmac Pol-derived epitope p68A (STPPLVRLV) and the human immunodeficiency virus type 1 (HIV-1) Env-derived p41A epitope (YAPPISGQI). The frequency of CD8(+) CTLs specific for the p11C,C-M, p68A, and p41A epitopes was quantitated in the same animals with a panel of tetrameric Mamu-A*01/peptide/β2m complexes. All SHIV-infected Mamu-A*01(+) rhesus monkeys tested had a high frequency of SIVmac Gag-specific CTLs to the p11C,C-M epitope. In contrast, only a fraction of the monkeys tested had detectable CTLs specific for the SIVmac Pol p68A and HIV-1 Env p41A epitopes, and these responses were detected at very low frequencies. Thus, the p11C,C-M-specific CD8(+) CTL response is dominant and the p41A- and p68A-specific CD8(+) CTL responses are nondominant. These results indicate that CD8(+) CTL responses to dominant CTL epitopes can be readily quantitated with the tetramer technology; however, CD8(+) CTL responses to nondominant epitopes, due to the low frequency of these epitope-specific cells, may be difficult to detect and quantitate by this approach.